Visual C++.NET the complete reference - Murray, William H. 1943- (McGraw-Hill/Osborne, 2002)
Visual C++7 enjoys a well-earned reputation as the premier language for creating the largest, most stable e-commerce Web sites. Expert authors have joined forces to write nearly 50 books, and have a loyal following. Completely revised to target the burgeoning e-commerce developer market, this title is packed with information on hot topics like debugging, Web support, attributed programming, and more.